Public awareness and misunderstanding about DrinkWise Australia: a cross‐sectional survey of Australian adults - Emily Brennan; Melanie A. Wakefield; Sarah J. Durkin; David H. Jernigan; Helen G. Dixon; Simone Pettigrew (Elsevier, 2017)
Abstract Objective: DrinkWise Australia is an alcohol industry Social Aspects/Public Relations Organisation (SAPRO). We assessed the Australian public's awareness of DrinkWise, beliefs about its funding source, and associations between funding beliefs and perceptions of DrinkWise. Methods: A total of 467 adult weekly drinkers completed an online cross‐sectional survey in February 2016. Results: Half the sample had heard of DrinkWise (48.6%); of these, the proportion aware that DrinkWise is industry funded (37.0%) was much smaller than the proportion believing it receives government funding (84.1%). Respondents who incorrectly believed DrinkWise receives government funding were more likely to hold a favourable perception of the organisation's credibility, trustworthiness and respectability than those who did not believe it receives government funding (75.9% vs. 58.3%; p=0.032). Conclusions: The drinking population is vulnerable to believing that alcohol industry public relations organisations such as DrinkWise are government funded, which in turn is associated with more favourable perceptions of the organisation's credibility, trustworthiness, and respectability. Implications for public health: Favourable perceptions of DrinkWise may enhance the industry's ability to delay or dilute potentially effective alcohol control policies. Future research should investigate whether educating the public about DrinkWise's alcohol industry funding alters the public's perception of how credible, trustworthy and respectable the organisation is.